2022
DOI: 10.14295/bjs.v1i12.243
|View full text |Cite
|
Sign up to set email alerts
|

Prospecção fitoquímica, teor de bixina e atividade alelopática de extratos de Bixa orellana L.

Abstract: Sementes de Bixa orellana possuem alto teor de bixina em uma fina camada externa. Sabe-se que alguns carotenoides apresentam ação alelopática em sementes de vegetais. Este estudo teve por objetivo realizar através da prospecção fitoquímica qualitativa, determinar o teor de bixina quantitativamente e avaliar a partir dos extratos aquoso e etanólico 95% das sementes trituradas de B. orellana sobre o efeito alelopático sobre duas sementes de grandes culturas. Sementes de B. orellana foram trituradas e os extratos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Here, our plant B. orellana exhibit this potential through many of it's group having important phytomolecules for several sectors such as pharmaceutical, agricultural and food. Our findings corroborate the study by Santos et al (2022) where they found results similar to ours for the phytochemistry of B. orellana seed extract, although our results were more complex for other phytochemical groups. According to Gutierrez-del-Rio et al ( 2021) and Stoll et al some phytochemical groups such as terpenoids (monoterpenes or carotenoids) such as bixin and norbixin present in B. orellana seeds have antioxidant action.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Here, our plant B. orellana exhibit this potential through many of it's group having important phytomolecules for several sectors such as pharmaceutical, agricultural and food. Our findings corroborate the study by Santos et al (2022) where they found results similar to ours for the phytochemistry of B. orellana seed extract, although our results were more complex for other phytochemical groups. According to Gutierrez-del-Rio et al ( 2021) and Stoll et al some phytochemical groups such as terpenoids (monoterpenes or carotenoids) such as bixin and norbixin present in B. orellana seeds have antioxidant action.…”
Section: Discussionsupporting
confidence: 93%
“…Color is an important parameter to be evaluated, as it influences product acceptance (ROMANI et al, 2018;RAMBABU et al, 2019;SANTOS et al, 2022). The biodegradable packaging used is usually transparent so that the product can be seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation